Comparison of the Achilles tendon moment arms determined using the tendon excursion and three‐dimensional methods. Issue 8 (5th October 2016) - Hashizume, Satoru; Fukutani, Atsuki; Kusumoto, Kazuki; Kurihara, Toshiyuki; Yanagiya, Toshio
Abstract: The moment arm of muscle‐tendon force is a key parameter for calculating muscle and tendon properties. The tendon excursion method was used for determining the Achilles tendon moment arm (ATMA). However, the accuracy of this method remains unclear. This study aimed to investigate the magnitude of error introduced in determining the ATMA using the tendon excursion method by comparing it with the reference three‐dimensional (3D) method. The tendon excursion method determined the ATMA as the ratio between the Achilles tendon displacement during foot rotation from 15° of dorsiflexion to 15° of plantarflexion and the joint rotation angle. A series of foot images was obtained at 15° of dorsiflexion, the neutral position, and 15° of plantarflexion. The 3D value of the ATMA was determined as the shortest distance between the talocrural joint axis and the line of action of the Achilles tendon force. The ATMA determined by the tendon excursion method was smaller by 3.8 mm than that determined using the 3D method. This error may be explained mainly by the length change in the Achilles tendon due to the change in the force applied to it, as passive plantarflexion torque was different by 11 Nm between 15° of dorsiflexion and 15° of plantarflexion. Furthermore, the ATMAs determined using the 3D and tendon excursion methods were significantly correlated but the coefficient of determination was not large ( R 2 = 0.352). This result suggests that the tendon excursion method may not be feasible to evaluate the individual variability of the ATMA. Abstract : This study aimed to confirm the magnitude of error introduced in determining the Achilles tendon moment arm (ATMA) using the tendon excursion method by comparing with the reference three‐dimensional method. Present result revealed that the tendon excursion method introduces 10% of underestimation for the determination of the ATMA.